Kultura organizacyjna struktur sieciowo-wirtualnych - Antczak, Zbigniew (The organizational culture virtual-network structures, 2006)
The author presents the unique results of research on organizational cultures in virtual-network structures and he presents his own reflections on the subject.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1132, s. 11-18